أمراض الفقر في المجتمعات النامية - صولة, فيروز; خياري, رقية (Sciences de l'Homme et de la Société, 2011)
قد تطور ميدان بحوث الأمراض  الناجمة عن الفقر تطورا ملحوظا في السنوات الأخيرة و ذلك بسبب قوة انتشارها و عودة أمراض قديمة بعد أن كانت عبئ على الِقصر المادي والتطور الطبي والتكنولوجي في العصور الماضية، وأهمها: الكوليرا، والجوع، بل الجوع حتى الموت في البلدان الأكثر فقرا .فالمرض و الفقر يرتبطان ببعضهما البعض ارتباطا وثيقا فالمرض يوفر البيئة المناسبة لانتشار الأمراض المعدية ويحول بين حصول السكان الفقراء على خدمات الوقاية و الرعاية الملائمة و في المقابل تصيب الأمراض المعدية بصورة رئيسية الفقراء  كما تعتبر احد أهم أسباب الفقر .   The field of researches of diseases caused by poverty has developed and witnessed a remarkable development in the last years, that is due to its strong spread and the returning of ancient diseases that were before a burden on the material inability and the medical and the technological progress in the past ages mainly. Cholera, hunger, starvation in the most poor countries, Somalia as an example the hard physical  pains the hard physical that they cause, in addition to the server deformity and the extreme incapacity such as onchocerciasis, schistosomiasis, and lymphatic disease Alkhitatulcers, Cagas disease, , Aleshmanaat disease, typhus, and kidney failure Tuberculosis,  malnutrition. The sickness and poverty are extremely linked to each other since the sickness provides the suitable environment to the spread of the infectious diseases and block the poor Inhabitants from getting the precaution services and the appropriate care, in the other hand the infectious diseases touch mainly the poor people and they are considered as one of the essential causes of poverty.